A Profile of the Organic Produce Consumer - Martina Zámková; Martin Prokop; Radek Stolín (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2018)
Our paper explores the factors influencing the consumers who buy organic food. Analysis of these factors enabled us to sort the consumers into groups based on their gender, age, education, and other identifiers. Further research then revealed more detailed shopping preferences of each one of those groups. The findings generated recommendations for producers and organic produce vendors on the best way to provide target marketing for different groups of consumers and therefore increase their sales of organic produce and food made from organic produce. Considering the use of categorical data, contingency tables and correspondence maps served as the best representation and processing tools. Data analysis showed that organic produce is most frequently purchased by respondents in the age of 45+ years, who also tend to spend more money for this range of products. At the same time, these would be the respondents, who struggle the most when recognizing organic produce and who have often never seen any advertisement for it. The respondents aged 25 years and less tend to purchase organic produce least frequently; they also often do not care about the origin of organic produce. Almost the same applies to families with multiple children. However, young respondents often grow their own organic produce. There is still a not insignificant percentage of consumers, who consider organic produce to be expensive and who do not believe in their qualities. As it turns out, when it comes to organic produce the respondents purchase most frequently fruits and vegetables, milk and dairy products.